Spain : inter-departmental correspondence (copy) - Carthy, A. E.
017b-0026-001 A.E. CARTHY Mr. H.V. TEWSON International 19 January, 1939. SPAIN. Mr. SCHEVENELS, after our conversation about the statements of relief, said that Mr. GILLIES had been talking by 'phone with ADLER this morning, asking for an urgent meeting between the Presidents and General Secretaries of the two Internationals, with a representative each of the French and British Trade Unions and Labour Parties, to see whether anything can be done for Spain at once. The meeting is intended to find some ways and means of giving Spain the material it needs, and the date proposed was next Tuesday, at the I.F.T.U. office. Gillies replied that it would be impossible for any of the British delegates to leave London on Monday, Tuesday, or Wednesday of next week. Schevenels wants to know from you and Mr. Hicks whether it is possible either to have a meeting on: 6 p.m. - TUESDAY afternoon, after 3 o'clock, in LONDON; (Schevenels arrives in Paris from Spain in the early morning); or on WEDNESDAY, at any time, in LONDON; or on THURSDAY morning in PARIS (Jouhaux has to leave for Geneva, Governing Body, meeting). If, on the other hand, the British representatives could go to Paris on Tuesday, the meeting could be started at 10 a.m.. Will you let him know this afternoon, if possible by 4 o'clock? 292/946/17b/27